2017
DOI: 10.21037/jtd.2017.06.104
|View full text |Cite
|
Sign up to set email alerts
|

Role of cannabis in cardiovascular disorders

Abstract: The growing popularity of medical and recreational consumption of cannabis, especially among the youth, raises immediate concerns regarding its safety and long-terms effects. The cardiovascular effects of cannabis are not well known. Cannabis consumption has been shown to cause arrhythmia including ventricular tachycardia, and potentially sudden death, and to increase the risk of myocardial infarction (MI). These effects appear to be compounded by cigarette smoking and precipitated by excessive physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 100 publications
3
129
0
5
Order By: Relevance
“…Pathway enrichment revealed that hypermethylation in cannabis-only users was overrepresented in genes associated with cardiomyopathies and neural signalling. This is consistent with the literature which raises clinical concerns around cardiac complications potentially associated with cannabis use 100103 . The enrichment of genes associated with neural signalling pathways is also consistent with the literature, including previous analyses of the CHDS cohort, which report associations between cannabis exposure and brain related biology such as mood disorders 7; 12; 48; 49; 5154; 104; 105 .…”
Section: Discussionsupporting
confidence: 92%
“…Pathway enrichment revealed that hypermethylation in cannabis-only users was overrepresented in genes associated with cardiomyopathies and neural signalling. This is consistent with the literature which raises clinical concerns around cardiac complications potentially associated with cannabis use 100103 . The enrichment of genes associated with neural signalling pathways is also consistent with the literature, including previous analyses of the CHDS cohort, which report associations between cannabis exposure and brain related biology such as mood disorders 7; 12; 48; 49; 5154; 104; 105 .…”
Section: Discussionsupporting
confidence: 92%
“…Слід пам'ятати, що дози опіоїдів для знеболювання в післяопераційному періоді можуть бути вищими в осіб, які вживають канабіс. Отже, дуже важливим для анестезіолога є діагностичні заходи та вміння запідозрити вживання канабісу [42].…”
Section: науковий огляд / Scientific Reviewunclassified
“…After years of exploration and practice, there is still room for improvement of symptomatic treatment methods including pharmacotherapy, percutaneous catheter ablation, or pacemaker implantation (Nattel and Carlsson 2006;Carlsson et al 2010;Yamada and Kay 2012;Vernooy et al 2014). Many factors can disrupt cardiac rhythms, including myocardial ischemia, prescription drugs, electrolyte disorders, smoking, alcohol, coffee, physical exercise, mental stimulation, ion channel abnormalities, or genetic defects (Kathiresan and Srivastava 2012;Peyronnet et al 2016;Weisbrod et al 2016;Chrysant 2017;Du et al 2017;Goyal et al 2017). Undoubtedly, defects of cardiac pacemaker cells and the corresponding tissues also disrupt cardiac rhythms (Yazawa et al 2011;Vedantham 2015).…”
Section: Introductionmentioning
confidence: 99%